Pelaksanaan Perlindungan Konsumen Atas Pemberian Garansi Produk Kasur In The Box Pada Atria Furniture - Sabrian, Farhan Abdillah; Lestari, Rika; Darnia, Meriza Elpha (Jurnal Ilmiah Wahana Pendidikan, 2026)
Consumer protection is an important part of creating a balance between the rights and obligations between consumers and business actors. In practice, there are still many consumers who have not received optimal protection, especially in terms of fulfilling their rights to information, services, and product guarantees. One form of protection that often becomes a problem is product warranty. This study aims to determine the implementation of consumer protection for the provision of product warranty for mattresses in the box at Atria Furniture and the responsibility of business actors for this. This research uses a sociological legal approach, namely by looking at the law as a social symptom that can be documentation in the interaction between consumers and business actors. Data were obtained through interviews with six consumers who submitted warranty claims, as well as managers and employees of Atria Furniture in Pekanbaru. The data was analyzed using a descriptive method with a qualitative data analysis approach that aims to systematically describe the facts in the field. The results showed that the implementation of the mattress in the box product warranty by Atria Furniture has not fully reflected the principles of consumer protection as stipulated in Law Number 8 of 1999 concerning Consumer Protection. Consumers experience difficulties in claim procedures, lack of information transparency, and slow and unsatisfactory responses from business actors. Based on these findings, it is necessary to evaluate the warranty service mechanism and increase the responsibility of business actors so that legal protection for consumers can be realized optimally.